Hubungan Penataan Tempat Duduk Siswa Terhadap Efektifitas Belajar Siswa SMK Negeri 1 Ngasem - Putra, Alfarrij Langgeng Pratama Wahyu; Ichwanto, Muhammad Aris; Sudarto, Sudarto (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
The arrangement of seating in the classroom has an important role in increasing the effectiveness of student learning, especially in the Vocational High This study aims to explore the relationship between seating arrangement and student learning effectiveness. Using the interview method, this study collected data from students and teachers regarding the impact of the U-Shape and Cluster structuring models. The results of the study showed that the U-Shape arrangement increased student engagement, focus, and interaction with the teacher, while the Cluster arrangement supported collaboration and comfort in group work. Students also recommend a combination of the two models to create a more optimal learning environment. These findings emphasize the importance of considering seating arrangement as a strategic factor in the effective learning process in vocational schools.School (SMK) environment such as SMK Negeri 1 Ngasem.